Practical support for breastfeeding mothers in achieving exclusive breastfeeding: A scoping review - Nur Intan Kusuma; Nidatul Khofiyah (Faculty of Medicine, Universitas Islam Indonesia, 2022)
Breast milk is the best food for babies aged 0-6 months and can be given until two years old with complementary food after the baby is 6 months old. Exclusive breastfeeding is a condition when a baby only receives breastmilk for six months. Exclusive breastfeeding is still a global problem because of the low coverage of exclusive breastfeeding. It can be optimized through social support, especially practical support. This scoping review aimed to map the literature, identify knowledge gaps, and review scientific evidence on practical support for breastfeeding mothers in achieving exclusive breastfeeding. The method of this review applied the Arksey and O'Malley’s framework. Four databases such as PubMed, Wiley Online Library, EBSCO, ScienceDirect and grey literature from google scholar were used to search relevant articles by using PEOS. The articles obtained were 1384 articles, and five articles matched the inclusion criteria. The critical appraisal for the five articles indicated four Grade A articles and one Grade B article. The research methods found in the articles were qualitative (60%), quantitative (20%) and mixed method (20%). In addition, three themes of the articles were found in this scoping review, namely the diverse forms of practical support, the benefits of practical support and the expected practical support. Practical support from husbands, families, health workers and communities is suggested for the mothers to achieve exclusive breastfeeding.